Model Universiti Wakaf di Malaysia : Universiti College Bestari, Terengganu - Wan Yusoff, Wan Zahari; Mazlan , Nur Amirah; Omar, Abdul Jalil (Research in Management of Technology and Business, 2021)
Abstract: Waqf is proven to have contributed in various fields including in the field of education. The budget to manage higher education today is very burdensome for the government where almost 95% of the management budget comes from the government, only 5% comes from income generation by the university. Therefore, an alternative mechanism is explored and educational endowment (waqf) is seen as having the potential to address this issue. To date, the majority of universities in Malaysia have begun to implement educational waqf but it is still in its early stages and there is still much to explore. Therefore, this study attempts to explore the best models and management strategies of universities abroad through waqf model. While at the local level, this study will examine the model used by Universiti College Bestari through waqf instruments. The methodology of this study uses a qualitative approach in which an interview guide instrument is formulated to obtain information from the respondents. The respondents of the study consisted of the management of Universiti College Bestari who were interviewed face to face where this institution is a case study in this research. In obtaining information on waqf university models abroad, sources of information are obtained through the journals articles, presentation papers and also information websites from the universities concerned. The information obtained was analyzed using content analysis. The results of the study found that the best educational waqf model for foreign universities is through endowment/waqf investment instruments. For Universiti College Bestari, the model used is the sales instrument of ‘wakaf kaki’, agriculture, livestock and business. The results of this study are expected to contribute to the body of knowledge in the context of a model of educational waqf/endowment that can be emulated.